ANALISIS PENGUKURAN RETURN ON INVESMENT MELALUI AKUNTANSI SUMBER DAYA MANUSIA DI KOPERASI - Risnaningsih, Inne (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
Cooperative Human Resources consists of Management / Supervisors, Employees and Members who are consistently involved in the process of achieving the goals of the cooperative, namely improving the welfare of Members in particular and society in general. Cooperative HR through its skills is a Human Intellectual / Human Asset for cooperatives that can be measured in costs (investment) and its value in Accounting is the same as measuring the assets / other assets owned by cooperatives. As a form of appreciation for the existence of cooperative human resources as human capital, it is hoped that special treatment will be assessed economically and presented in the Financial Statements (Balance Sheet) which will then be compared to Return on Investment (ROI) to measure cooperative performance with the HR Accounting approach as a solution to overcome weaknesses ROI measurement if done conventionally.